2011
DOI: 10.1186/1477-7819-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Physician attitudes and treatment patterns for pancreatic cancer

Abstract: BackgroundSurgery appears to be an underutilized treatment option for pancreatic cancer. Nihilistic physician attitudes may be partly responsible. The study objectives were to analyze physician attitudes towards this disease and determine treatment patterns and outcomes including rates of surgical referral.MethodsA survey was administered to 420 physicians in Manitoba to document general knowledge and attitudes. Population based administrative data was accessed for all patients diagnosed with pancreatic cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Yet, in spite of modest progress in these ancillary oncological modalities, surgical intervention, the primary contributor to potential cure, is largely underutilized for pancreatic cancer in the United States . This may reflect outdated beliefs regarding post‐operative morbidity and mortality rates from the physician referral base …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, in spite of modest progress in these ancillary oncological modalities, surgical intervention, the primary contributor to potential cure, is largely underutilized for pancreatic cancer in the United States . This may reflect outdated beliefs regarding post‐operative morbidity and mortality rates from the physician referral base …”
Section: Introductionmentioning
confidence: 99%
“…16 This may reflect outdated beliefs regarding post-operative morbidity and mortality rates from the physician referral base. 17 Furthermore, the reporting standards for surgical outcomes have changed in recent years to address ambiguities in surgical terminology. The Toronto group has developed and subsequently refined an increasingly popular complication grading scale based on clinical impact.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the introduction of new combination chemotherapies, median survival of patients with APC remains less than 1 year. Patients with pancreatic cancers remain unfortunate in that despite eligibility, many patients are not offered radical treatments even at early stages of diagnosis [20]. Therefore it is not surprising that these patients are declined VTE prophylaxis by the attending physicians at their advanced stages.…”
Section: Editorialmentioning
confidence: 99%
“…Except for surgery, other treatments have shown modest impact on patients' survival and are often underutilized [3][4][5][6][7][8][9]. Since there are no cost-effective screening tests, a high clinical suspicion is necessary for the diagnosis of early stage tumors2 and the majority of patients are diagnosed with locally advanced or metastatic disease [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Besides established prognostic factors such as cellular differentiation, lymph vascular infiltration and tumor stage, there may be other reasons responsible for the low survival rate of these patients. Several groups have reported that PC patients receive one of the lowest rates of cancer-directed therapy among all the solid tumors [4][5][6][7][8][9][10] and treatments may differ based upon patients' socioeconomic status (education level, income), place of residence (rural vs. urban), number of procedures performed in a health system (low vs. high volume hospital) and physician expertise [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%